Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/(sici)1097-4636(200001)49:1<79::aid-jbm10>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cell adhesion complexes in epithelial cells seeded on biomaterial surfaces

Abstract: Abstract:Clinical studies indicate that soft tissue responses around dental implants vary, depending on the material used. It is therefore also possible that there are differences in how epithelial cells attach to various biomaterial surfaces. We studied the adhesion of cultured epithelial cells to five different dental material surfaces and to glass. The efficacy of adhesion was evaluated by using scanning electron microscopy (SEM) and immunofluorescence microscopy (IF) with antibodies to vinculin and ␣ 6 ␤ 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…With pooled human cells, this up-regulation was significant for both focal adhesion and hemidesmosome expression at 4 h, and for matched ovine cells, at all time-points. Raisanen et al showed that focal adhesions develop earlier than hemidesmosomes in epidermal keratinocytes, and this is consistent with the results of our current study (Raisanen et al, 2000). Pendegrass et al demonstrated that hemidesmosome and focal adhesion expression significantly increase over time for immortalised human keratinocytes cultured on titanium alloy (Pendegrass et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…With pooled human cells, this up-regulation was significant for both focal adhesion and hemidesmosome expression at 4 h, and for matched ovine cells, at all time-points. Raisanen et al showed that focal adhesions develop earlier than hemidesmosomes in epidermal keratinocytes, and this is consistent with the results of our current study (Raisanen et al, 2000). Pendegrass et al demonstrated that hemidesmosome and focal adhesion expression significantly increase over time for immortalised human keratinocytes cultured on titanium alloy (Pendegrass et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Based on this paper, augmentation strategies to promote earlier epidermal keratinocyte attachment may prove beneficial in developing a seal at the transcutaneous interface. The attachment of the marginal gingiva to a tooth surface is mediated by the thin non-keratinised JE, which attaches to the tooth surface through hemidesmosomes and the IBL ( Bosshardt et al, 2005;Ikeda et al, 2000;Masaoka et al, 2009;Oksonen et al, 2001;Shimono et al, 2003;Shiraiwa et al, 2002). The JE that develops around dental implants contains laminin-332 and is expressed by cells of the oral mucosa (Masaoka et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the possible higher transport activity combined with an increased cell adhesion, titanium may foster a highly bioactive growth environment compared to gold and aluminium. Several studies proved that titanium results in improved biocompatibility in the sense of growth rate and cell outgrowth compared to gold and aluminium (Niinomi 1999;Räisänen et al 2000).…”
Section: Discussionmentioning
confidence: 99%